TINJAUAN HUKUM ISLAM TERHADAP MAHAR DALAM PERKAWINAN ISLAM - Nurul Amalia; Nur Irmayanti Umar (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2024)
This article discusses the legal and social aspects of dowries in marriage, focusing on the provisions of Law No. 1 of 1974 and Government Regulation No. 9 of 1975, about as well as the influence of local customs such as "uang panai" in the Bugis-Makassar community. The study employs qualitative research methods, including interviews and literature reviews, to understand dowry practices from both legal and Islamic perspectives.   The findings reveal that dowries are often influenced by the social and economic status of the families involved, which can place a financial burden on the groom if the amount is excessively high. In Islamic law, there is no fixed minimum or maximum for dowries, and they can be given in the form of money or goods, depending on mutual agreement. However, the practice of uang panai in Bugis-Makassar culture can lead to issues such as marriage cancellations or financial difficulties. The article concludes that it is crucial to maintain balance in dowry determination to avoid placing undue burden on either party, ensuring that the dowry serves as a symbol of respect and responsibility without causing conflict.